Clinical and histological effects of the intrathecal administration of a single dose of dexmedetomidine in rabbits - de Pereira Cardoso, Hugo D. [UNESP]; Fim, Natalia C. [UNESP]; Marques, Mariangela A. [UNESP]; Miot, Hélio [UNESP]; de Vasconcelos Machado, Vânia M. [UNESP]; Solanki, Daneshvari R.; Lima, Rodrigo Moreira [UNESP]; de Carvalho, Ana L. [UNESP]; Navarro, Lais H. [UNESP]; Ganem, Eliana Marisa [UNESP] (My University, 2016)
Background: There is experimental evidence that dexmedetomidine has neuroprotective effects. So, it could be expected that its intrathecal or epidural administration presents no harm. However, whether dexmedetomidine is neurotoxic to the spinal cord remains to be fully elucidated. Objective: To evaluate the effect of preservative-free dexmedetomidine administered as a subarachnoid single injection on the spinal cord and meninges of rabbits. Study Design: Research article. Setting: Experimental research laboratory. Methods: Twenty young adult female rabbits, each weighing between 3200 and 4900 g, and having a spine length between 36 and 40 cm, were divided by lot into 2 groups (G): 0.9% saline in G1 and preservative-free dexmedetomidine in G2 (dose of 10 μg). After intravenous anesthesia with ketamine and xylazine, the subarachnoid space was punctured at S1-S2 under ultrasound guidance, and a random 5 μl.cm-1 of spinal length (0.2 mL) of solution (saline or dexmedetomidine) was injected. The animals remained in captivity for 21 days under medical observation and were sacrificed by decapitation. The lumbosacral spinal cord portion was removed for immunohistochemistry to assess the glial fibrillary acidic protein (GFAP), and histology was assessed using hematoxylin and eosin (HE) stain. Results: None of the animals had impaired motor function or decreased nociception during the period of clinical observation. None of the animals from the control group showed signs of injuries to meninges. In the dexmedetomidine group, however, 9 animals presented with signs of meningeal injury. The main histological changes observed were areas with meningeal thickening and lymphoplasmocitary infiltration in the pia-mater and arachnoid. Further histological examination also revealed adherence areas among the pia and arachnoid. There was no signal of injury in neural tissue in any animal of both groups. Limitations: Evaluation of the possible analgesic effects of the intrathecal dexmedetomidine was not performed. Conclusion: On the basis of the present results, dexmedetomidine administered in the subarachnoid space in a single dose of 10 μg is capable of producing histological changes over the meninges of rabbits.
Keywords: Anesthesia, spinal; Dexmedetomine; Injections, spinal; Rabbits; Spinal cord